RELATIONSHIP BETWEEN SELF ADJUSTMENT WITH QUALITY OF LIFE OFELDERLY PENSIONERSIN BARON VILLAGE MAGETAN - Duwi Basuki; Ita Wahyuni (STIKes William Booth Surabaya, 2016)
Retirement is one form of psychosocial changes of elderly could be a stressor if elderly was not ready for it and it’s also rising difficulties in adjusting to post retirement. Difficulties can cause tension or stress that reduced quality of life. This study aimed to know relationship between self adjustment with quality of life of elderly pensioners in Baron Village Magetan. Research design was analytic correlational with cross sectional approach. Population was all retirees as many as 48 people and taken all as samples by total sampling. The results showed majority have ineffective self adjustment as many as 30 respondents (62,5%), mostly have low quality of their life as many as 25 respondents (52,1%), and cross tabulation showed there was relationship between self adjustment with quality of life of elderly pensioners in Baron Village Magetan. Respondents who were not effective in adjusting to post retirement because they felt elimination on their professional identity, reduced self esteem and inability to get various needs of life that were previously easy to obtain. It lead to lower life satisfaction that represented lower quality of life. Elderly should learn various effective adjustment mechanism in order to live better retirement and improve quality of life.